The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11427-014-4609-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating design principles of micropatterned encapsulation systems containing high-density microtissue arrays

Abstract: Immunoisolation is an important strategy to protect transplanted cells from rejection by the host immune system. Recently, microfabrication techniques have been used to create hydrogel membranes to encapsulate microtissue in an arrayed organization. The method illustrates a new macroencapsulation paradigm that may allow transplantation of a large number of cells with microscale spatial control, while maintaining an encapsulation device that is easily maneuverable and remaining integrated following transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Hierarchical design of the topographical and spatial features of scaffolds therefore is a critical step in facilitating the tissue‐engineering and cell‐based therapy. First, a real cell transplantation regimen may involve up to 10 9 cells for treating one patient; the three‐dimensional (3D) organization of such a large number of cells governs the volume/shape of the final transplants, a critical factor that determines the implantability of a construct . In addition, optimal organization of cells also promotes efficient vascularization and prohibits hypoxia and insufficient nutrient supply caused by random cell clumping .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchical design of the topographical and spatial features of scaffolds therefore is a critical step in facilitating the tissue‐engineering and cell‐based therapy. First, a real cell transplantation regimen may involve up to 10 9 cells for treating one patient; the three‐dimensional (3D) organization of such a large number of cells governs the volume/shape of the final transplants, a critical factor that determines the implantability of a construct . In addition, optimal organization of cells also promotes efficient vascularization and prohibits hypoxia and insufficient nutrient supply caused by random cell clumping .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, although more and more patterned 3D matrices have been developed in the past through photo‐/soft‐lithographic and 3D printing processes, most of the resulting scaffolds may only allow for control over the localization of cells/microtissues: the desired local characteristics of the scaffolds, or the niche of cells are still hard to be incorporated . For example, the micropatterned hydrogel matrices may offer a limited range of local mass transport and mechanical properties . Similarly, plastic degradable scaffolds made from rapid‐prototyping may also lack local micro or nanotopographical features due to the resolution limitations in the fabrication process …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al . developed agarose hydrogel membranes with microwell patterns allowing for cells separation as a model encapsulation system 13 . Moreover, they suggested that micropatterned encapsulation systems may be able to minimize the transplantation volume, increase the encapsulation efficiency and improve the cell viability.…”
Section: Introductionmentioning
confidence: 99%